Reliance Commercial Corporation (Spice Trading Company) - Reliance Industries Limited (2022)
Dhirubhai Ambani starts a spice trading company, Reliance Commercial Corporation, at Masjid Bunder, Mumbai, in partnership with Trambhakbhai Damani.